Pancasila sebagai solusi krisis kepercayaan publik terhadap institusi demokrasi di indonesia - ferdinan, muhammad aditya (Maliki Interdisciplinary Journal, 2025)
Indonesian democracy, which has been running for more than two decades since the 1998 Reformation, faces a serious challenge in the form of a crisis of public trust in democratic institutions such as the House of Representatives (DPR), the government, and election organizers. This phenomenon is exacerbated by rampant corruption, political polarization on social media, and low transparency and public participation. As a result, political apathy has emerged, especially among the younger generation. This paper aims to analyze the causes of this crisis of trust and offer solutions through the revitalization of Pancasila values. Using a descriptive-analytical approach, this study explains how each Pancasila principle can serve as an ethical and practical bridge in strengthening the relationship between society and democratic institutions. The implementation of values ​​such as justice, unity, and deliberation is considered crucial in creating a transparent and inclusive political system. Furthermore, the implementation of strategic steps in the digital era—such as technology-based Pancasila education, anti-hoax campaigns, public policy transparency, and participatory online dialogue—can sustainably increase public trust. The results of the study show that Pancasila, if actualized contextually and digitally, has great potential to strengthen the moral and democratic foundations of the Indonesian nation amidst the challenges of the global information era.